Expectations and perspectives of ovarian cancer patients about cancer management in Romania. The international NOGGO‐ENGOT trial: EXPRESSION III. (10th August 2016) - Achimaş‐Cadariu, P.; Iancu, M.; Kubelac, P.; Pop, F.; Braicu, I.; Vlad, C.; Oskay‐Özcelik, G.; Sehouli, J.
Abstract : We have investigated a relational model of expectations and preferences among ovarian cancer patients centred on physician–patient communication, treatment approach, and the need for information. Consecutive patients anonymously filled in the EXPRESSION III questionnaire between 2009 and 2012. Following descriptive statistics, structural equation modelling was used to analyse the relationships between physician's evaluation by the patient (PEP), result of therapy (RT), need for changes in treatment (NCT) and patient's desire to be informed (PD). From a total of 108 patients, 53 (49.1%) knew their disease stage, 103 (95.4%) underwent surgery, 91 (84.3%) had chemotherapy and 51 (46.3%) relapsed. The final model demonstrated a good fit of data with fit indices >0.90. There was a significant positive effect of PEP on RT and a significant negative effect of PEP on NCT, with the final model explaining 84% of the NCT variance. Physicians represent the main point of contact, not only as a source of information about the disease and various treatment options, but also in the coping processes. As patients benefit from completeness of medical consultations, their awareness of the treatment outcome increases, while a negative perception of the physician leads to a desire to make changes in therapy.